Cossidae (Lepidoptera) of Iran: a review with description of two new species - Alipanah, Helen; Yakovlev, Roman; Falsafi, Hossein; Witt, Thomas; Saldaitis, Aidas (Zootaxa, 2021)
A taxonomic revision of the Iranian species of the family Cossidae is conducted. Sixthy-nine species and 16 subspecies in 26 genera and five subfamilies, namely Catoptinae, Mehariinae, Stygiinae, Cossinae and Zeuzerinae, are identified. Meharia baluchestana Alipanah & Yakovlev, sp. n. and Cossulus kopetdaghensis Yakovlev & Alipanah, sp. n. are described. Dyspessa elbursensis derbenti Daniel, 1964 is raised to the species level, Dyspessa derbenti Daniel, 1964, stat. n.; Dieida ledereri (Staudinger, 1817) is considered as the senior synonym of D. persa Strand in Stichel, 1911, syn. n.; Cossus coccus araraticus Teich, 1896 is considered as a senior synonym of C. c. armeniaca Rothschild, 1912, syn. n.; C c. kossai Wiltshire, 1957 as a senior synonym of C. c. omrana Wiltshire, 1957, syn. n.; and Deserticossus arenicola iranica (Austaut, 1897), syn. n. and D. arenicola transcaucasicus (Zukowsky, 1936), syn. n. are newly synonymized with D. arenicola arenicola (Staudinger, 1879). Additionally, the genus Mormogystia Schoorl, 1990, and 15 species, namely Dyspessa alpherakyi (Christoph in Romanoff, 1885), D. artemis Yakovlev, 2008, D. blonda Yakovlev, 2008, D. stroehlei Yakovlev, 2008, D. tsvetaevi Yakovlev, 2008, Barchaniella inspersa (Christoph, 1887), B. sacara (Grum-Grshimailo, 1902), Cossulus intractatus (Staudinger, 1887), C. mollis (Christoph, 1887), C. stertzi (Püngeler, 1899), Deserticossus campicola (Eversmann, 1854), Kotchevnik durelli Yakovlev, 2004, Mormogystia reibellii (Oberthür, 1876), Eremocossus erebuni Yakovlev, 2008 and Phragmataecia turkmenbashi Yakovlev, 2008 are newly reported for the fauna of Iran. Moreover, the hitherto unknown female of Kotchevnik durelli is described. Additional data of the species previously reported from Iran is provided and the collecting data maps of the entire studied species are presented.